Effect of operation conditions on Catalytic Oxidation of Phenol in Aqueous Solution - T. Mohammed, Wadood; A. Kadim, Hisham (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This work was conducted to study the oxidation of phenol in aqueous solution using copper based catalyst with zinc as promoter and different carrier, i.e. γ-Alumina and silica. These catalysts were prepared by impregnation method.The effect of catalyst composition, pH (5.6-9), phenol to catalyst concentration ratio (2-0.5), air feed rate (30-50) ml/s, stirring speed (400-800) rpm, and temperature (80-100) °C were examined in order to find the best conditions for phenol conversion.The best operating conditions which lead to maximum phenol conversion (73.1%) are : 7.5 pH, 4/6 phenol to catalyst concentration, 40 ml/s air feed rate, 600 rpm stirring speed, and 100 °C reaction temperature. The reaction involved an induction period and a steady state activity regime. Both of the regimes exhibiting first order behavior with respect to the phenol concentration. The rate constants k1 and k2 for the initial rate and steady state activity regime are represented by k1=1.9×10-3 ((cm3liq/gcat) 0.5s-1 and k2= 2.4×10-10 ((cm3liq/gcat) 2 s-1) respectively.